Politics, press and military participation in the abdication of d. Pedro I - Pandolfi, Fernanda Claudia [UNESP] (Univ do Vale do Rio Dos Sinos, 2012)
This work seeks to contribute to a better understanding of the Abdication, analyzing how and why sections of the army joined the liberal groups against the emperor, focusing on the period that immediately preceded this event. The argument is that the alliance between sections of the army and the liberal groups in 1831 was possible because the expansion of the "public space" in the city of Rio de Janeiro, a process in which newspapers such as "O Republico" played a key role as they became a privileged locus for political disputes. The article shows that that newspaper helped to build a political identity based on the defense of Brazilian interests against Portuguese despotism, giving momentum to internal conflicts around this subject that were already taking place among sections of the army and hence triggering the process that would lead to the Abdication.
Keywords: Brazil Empire; Abdication; military; press; d. Pedro I